OVERVIEW OF LACTATE DEHYDROGENASE (LDH) ENZYME ACTIVITY IN HYPERTENSIVE PATIENTS WITH OBESITY AT TANGERANG DISTRICT HOSPITAL - Maheswari Syifa Puspamurti; Ramadas A (Journal of Noncommunicable Diseases Prevention and Control, 2025)
Hypertension is a condition characterized by abnormally high blood pressure. One of the modifiable risk factors for hypertension is obesity. With increased body mass, the heart must pump blood harder, resulting in elevated blood pressure. One type of damage experienced by hypertension sufferers is endothelial dysfunction, which can be a predictor of atherosclerosis. This damage results in the release of the LDH enzyme into the blood. This study aims to determine the overview of LDH enzyme activity in hypertensive patients with obesity at the Tangerang District Hospital. The research design was descriptive and was conducted from March to May 2025. The data collection technique utilized purposive sampling with 26 respondents. The examination method used was the IFCC method. The results showed that LDH enzyme activity in hypertensive patients was high in 8 people (31%). Based on age, high results predominantly occurred in the pre-elderly group (46-60 years) with 5 people (63%). Based on gender, high results were primarily found in women, amounting to 7 people (88%). Based on obesity status, 8 people (100%) with Obesity I had high results. Based on antihypertensive medication consumption, high results were predominantly found in the amlodipine group with 5 people (63%). Future researchers can explore other unexplored factors such as physical activity, dietary patterns, and a history of vitamin C or alcohol consumption.